ANALISIS SETTING RECLOSER & PENENTUAN RATING FUSE CUT OUT BERDASARKAN ZONA GANGGUAN PADA JARINGAN DISTRIBUSI 20 KV GI SIDERA FEEDER PALOLO PT. PLN (PERSERO) BERBASIS ETAP 16.0.0 - Evie Angelina; Muhammad Sarjan (Foristek, 2019)
In the distribution of electrical energy from substations to the load center distribution channels are needed. The problem that often occurs in distribution channels is short circuit interference. Often the location of the disturbance cannot be immediately located, thus slowing down the process of handling the disturbance. Disturbances that occur in the 20 kV distribution network are temporary (temporary interruption) and permanent (permanent fixes that take a long time). Even the interference that was originally only temporary can turn into permanent interference, because the protection system installed does not work optimally. To overcome this, it is necessary to analyze the disturbance zone in the distribution network. Protection on the electricity distribution network has a very important role for the reliability and continuity as well as the security of electricity distribution, especially at the end of the load and one-phase branching. The inter-safety coordination on the distribution network must be in accordance with the standards set by PT PLN (Persero) ). In one phase branching area there is a safety against the current interference that may occur, namely Fuse Cut Out (FCO). very small short circuit, for that we need to pay attention to the way the recloser works with FCO (fuse Cut Out) so that the two safeguards can work well and avoid coordination failures on one-phase branching lines, so that the blackout area can be reduced. do the OCR relay settings in recl oser and Determination of suitable FCO rating so that the type used can be in accordance with the standard and can be in accordance with the load conditions in the field.